"Just tell me what's going on": The views of parents of children with genetic conditions regarding the research use of their child's electronic health record. (8th January 2020) - Andrews, Sara M; Raspa, Melissa; Edwards, Anne; Moultrie, Rebecca; Turner-Brown, Lauren; Wagner, Laura; Alvarez Rivas, Alexandra; Frisch, Mary Katherine; Wheeler, Anne C
Abstract: Objective: The purpose of this study was to understand the ethical, legal, and social issues described by parents of children with known or suspected genetic conditions that cause intellectual and developmental disabilities regarding research use of their child's electronic health record (EHR). Materials and Methods: We conducted 4 focus groups with parents of children with a known (n = 12) or suspected (n = 11) genetic condition, as well as 2 comparison groups with parents who had a child with no known genetic condition (n = 15). Focus group transcripts were coded and analyzed using directed content analysis. Results: After weighing the risks and benefits, parents of children with known or suspected genetic conditions were willing to share their child's EHR for research studies under certain conditions. Preferences were for studies conducted by universities or nonprofits that might benefit their child or others with the same condition. Parents also valued return of research results. Discussion: Trust, transparency, altruism, and concerns about privacy emerged as factors that affect parents' willingness to allow research use of their child's EHR. Conclusion: Researchers should consider how to build trust with parents by increasing transparency of the research process and explaining specifically how they will ensure the confidentiality of EHR data.